Welfare and Moral Economy. Issue 1 (2nd January 2018) - Sayer, Andrew
ABSTRACT: The paper offers a wide-angle view of ethics and welfare through the lens of 'moral economy'. It examines economic activities in relation to a view of welfare as well-being, and to ethics in terms of economic justice. Rather than draw upon abstract ideal theories such as Rawlsian or Capabilities approaches, it calls for an evaluation of actually existing sources of harm and benefit in neoliberal capitalism. It argues that we need to look behind economic outcomes in terms of how much money different people have, examine their economic relations to others, and evaluate the justifications of these relations and their associated rights and practices. It distinguishes three sources of income – earned income, transfers, and unearned income, and argues that the last of these has no functional or ethical justification but has major implications for welfare. It then comments on the policy implications of the argument, including brief comments on asset-based welfare and universal basic income policies, and concludes.